Investigating target refraction advice provided to cataract surgery patients by UK optometrists and ophthalmologists. (18th February 2022) - Charlesworth, Emily; Alderson, Alison J; Fylan, Fiona; Armstrong, Richard A; Chandra, Aman; Elliott, David B
Abstract: Purpose: To determine whether UK optometrists and ophthalmologists provide target refraction advice to patients prior to cataract surgery, and when this should first be discussed. Methods: Optometrists and ophthalmologists were asked to complete a survey of two clinical vignettes (both older patients with cataract; a pre‐operative myope who routinely read without glasses and a patient using a monovision approach), plus multiple choice and short answer questions either using hard copy or online. Results: Responses were obtained from 437 optometrists and 50 ophthalmologists. Optometrists who reported they would provide target refraction advice were more experienced (median 22 years) than those who would leave this to the Hospital Eye Service (median 10 years). The former group reported it was in the patients' best interest to make an informed decision as they had seen many myopic patients who read uncorrected pre‐operatively, and were unhappy that they could no longer do so after surgery. Inexperienced optometrists reported that they did not want to overstep their authority and left the decision to the ophthalmologist. The ophthalmologists estimated their percentage of emmetropic target refractions over the last year to have been 90%. Conclusion: Currently, some long‐term myopes become dissatisfied after cataract surgery due to an emmetropic target refraction that leaves them unable to read without glasses as they did prior to surgery. Although experienced optometrists are aware of this and attempt to discuss this issue with patients, less experienced optometrists tend not to. This suggests that target refraction needs greater exposure in university training and continuing professional development. To provide patients with the knowledge to make informed decisions regarding their surgery, we suggest an agreed protocol within funded direct referral schemes of initial target refraction discussions by optometrists to introduce the idea of refractive outcomes and outline options, with further discussion with the ophthalmologist to clarify understanding.